2014
DOI: 10.1186/1757-2215-7-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the leptin receptor in human ovaries affected by endometrioma and detection of high levels of leptin in the ovarian endometriomal fluid

Abstract: BackgroundThis study was designed to investigate leptin levels in the fluid in ovarian endometriomas (OEs) and to compare the expression of leptin and its receptors (OBR) in ovarian tissue affected by endometrioma in infertile women to its expression in the normal ovarian tissue of fertile controls without endometriosis.MethodsIn this case–control observational study, ovarian tissue, blood samples and peritoneal fluid were obtained from 20 women (10 fertile controls without endometriosis or any ovarian disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“… 35 , 36 , 42 The presence of leptin variation in obese women indicates factors other than adiposity are implicated in leptin variation during menstruation. Corpus luteum formation during the luteinization phase could be possible cause of elevated leptin, and corpus luteum has been found to produce leptin in human 46 and bovine models. 47 Further support came from comparing ovulatory and anovulatory cycles; decreased leptin concentration was found during the anovulatory cycle (ie, without ovulation and corpus luteum) compared to the corresponding higher leptin level during the luteal phase of the ovulatory cycles (with ovulation and corpus luteum formation).…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 36 , 42 The presence of leptin variation in obese women indicates factors other than adiposity are implicated in leptin variation during menstruation. Corpus luteum formation during the luteinization phase could be possible cause of elevated leptin, and corpus luteum has been found to produce leptin in human 46 and bovine models. 47 Further support came from comparing ovulatory and anovulatory cycles; decreased leptin concentration was found during the anovulatory cycle (ie, without ovulation and corpus luteum) compared to the corresponding higher leptin level during the luteal phase of the ovulatory cycles (with ovulation and corpus luteum formation).…”
Section: Discussionmentioning
confidence: 99%
“…In Zendron et al's [ 11 ] study, 25 women were enrolled , 10 as control and 15 patients undergoing surgery for adnexal mass, and the leptin levels in both serum and peritoneal fluid (PF) and the protein expression in different peritoneal implants were studied. The study revealed that the level of leptin was higher in the endometriosis group but had no clear role in the progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently we have published a study on endometriosis stage IV patients [ 29 ] in which we found that that leptin levels in both the serum and PF were changed. In addition, in the cystic fluid of endometrioma, the leptin levels were very high compared to the serum and PF.…”
Section: Discussionmentioning
confidence: 99%
“…Together with data from literature [ 13 ], these data suggest that the presence of peritoneal disease, and not of an ovarian implant, is the factor that influences the concentration of leptin in the serum and PF in endometriosis. This result and the fact that the cystic fluid of endometrioma has high levels of leptin compared to serum and PF [ 29 ] suggest that the leptin produced by the ovary implant could be sequestered to the endometrial cyst instead of going to the serum or peritoneal fluid.…”
Section: Discussionmentioning
confidence: 99%